2002
DOI: 10.1021/ja028089r
|View full text |Cite
|
Sign up to set email alerts
|

Direct Detection by Atomic Force Microscopy of Single Bond Forces Associated with the Rupture of Discrete Charge-Transfer Complexes

Abstract: Atomic force microscopy (AFM) was used to measure the chemical binding force of discrete electron donor-acceptor complexes formed at the interface between proximal self-assembled monolayers (SAMs). Derivatives of the well-known electron donor N,N,N',N'-tetramethylphenylenediamine (TMPD) and the electron acceptor 7,7,8,8-tetracyanoquinodimethane (TCNQ) were immobilized on Au-coated AFM tips and substrates by formation of SAMs of N,N,N'-trimethyl-N'-(10-thiodecyl)-1,4-phenylenediamine (I) and bis(10-(2-((2,5-cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 51 publications
1
58
1
Order By: Relevance
“…The work of Skulason and Frisbie [388] deals with the adhesion between gold and S-acetate-, Oacetate-, SH-and OH-terminated SAMs in different solvents, and the accent is put on the detection of the discrete rupture forces or force quanta (see also [389]). The authors found a force quantum of 0.1 nN in histograms of the adhesion force and assigned it to the rupture of individual chemical bonds.…”
Section: Determination Of Hamaker Constants Adhesion and Surface Enementioning
confidence: 99%
See 1 more Smart Citation
“…The work of Skulason and Frisbie [388] deals with the adhesion between gold and S-acetate-, Oacetate-, SH-and OH-terminated SAMs in different solvents, and the accent is put on the detection of the discrete rupture forces or force quanta (see also [389]). The authors found a force quantum of 0.1 nN in histograms of the adhesion force and assigned it to the rupture of individual chemical bonds.…”
Section: Determination Of Hamaker Constants Adhesion and Surface Enementioning
confidence: 99%
“…Several experiments also have been performed with DNA strands [1078,[1143][1144][1145][1146], DNA-ligands [1147][1148][1149][1150], RNA [1151], RNA-ligands [1152], peptides [1153], and other complementary molecules [389,1154,1155]. In particular, Schumakovitch et al [1156] have studied the temperature dependence of unbinding forces between complementary DNA strands.…”
Section: Rupture Force Of Specific Interactionsmentioning
confidence: 99%
“…20,23,[28][29][30][31][32][33][34][35]37,38 We have evaluated the single force for specific hydrogen bonding between the phenylurea and carboxyl groups by a statistical method using autocorrelation analysis of the values of the adhesion force. In this analysis, an autocorrelation function is computed for the histogram data of the observed pull-off forces.…”
Section: Single Force Of Hydrogen Bonding On Mixed Mha/ht Sams (Cooh/mentioning
confidence: 99%
“…The values for the single force determined here are in a similar order of magnitude to the single rupture forces of the bond in various molecule pairs, 12,24 including the complementary DNA bases, 23 which were determined by AFM using chemically modified tips. According to the equation E = Fsd, 29,34 assuming that the distance (d) is approximately 0.1 nm, the product of Fs (the single force) and d affords an approximate bond energy (E) of 3 -4 kJ mol -1 , which is in a reasonable order of magnitude for the energy of general hydrogen bondings.…”
Section: Single Force Of Hydrogen Bonding On Mixed Mha/ht Sams (Cooh/mentioning
confidence: 99%
See 1 more Smart Citation